Towards the Structure of Black Holes in Asymptotically Safe Gravity - Adeifeoba, Ademola (My University, 2018)
Asymptotically safe quantum gravity suggests a resolution to the classical spacetime singularity of Schwarzschild-(A)dS black holes. In particular, this is realizable only for a vanishing microscopic value of the dimensionless cosmological constant at the asymptotically safe fixed point. To accommodate a nonzero infrared value of the cosmological constant, we consider the linearized Renormalization Group flow away from the fixed point, which is characterized by two critical exponents in the Einstein-Hilbert truncation. In this study, we show that the realization of a regular de-Sitter core places a bound on the universal gravitational critical exponents. Accordingly, our study hints at the possibility of singularity resolution in black holes, as explicit estimates of the critical exponents in the literature point towards a realization of our bound.
Supplemental Materials: https://osf.io/a6fk9/
Keywords: Asymptotic Safety; Black Hole Singularity; Quantum Gravity; Renormalization Group; Ultraviolet Fixed Point